KEBIASAAN SARAPAN, STATUS GIZI, DAN KUALITAS HIDUP REMAJA SMP BOSOWA BINA INSANI BOGOR - Niswah, Ilyatun; Damanik, Muhammad Rizal Martua; Ekawidyani, Karina Rahmadia (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The objective of this study was to examine the association between breakfast habits, nutritional status, and health related quality of life of adolescents in Bosowa Bina Insani Junior High School Bogor. A cross sectional study was conducted and simple random sampling was used to determine the subjects. Subjects were 60 adolescent students of Bosowa Bina Insani Junior High School Bogor aged 13—15 years old. The study found there was no significant difference in nutritional status between breakfast skippers and breakfast eaters (p>0.05). However, regular breakfast eaters were more likely to have lower body weight (r=-0.160, p=0.222). There was no significant difference of health related quality of life based on nutritional status (p>0.05). Breakfast eaters tended to have better quality of life than breakfast skippers even though there was no significant difference between them (p>0.05).